Foundations for practice in occupational therapy. - Hagedorn, Rosemary, ....- (New York : Churchill Livingstone, 1997)
Contents: --------- I. OCCUPATIONAL THERAPY : AN OUTLINE OF THEORY AND PRACTICE 1. Introduction 2. The occupational therapy process 3. Core skills and processes 4. The philosophical and theoretical basis for practice 5. Linking theory with practice II. CONCEPTUAL FOUNDATIONS FOR PRACTICE 6. Primary frames of reference 7. Applied frames of reference which focus on physical dysfunction 8. Applied frames of reference which focus on psychosocial dysfunction 9. Processes of change 10. Occupational therapy models
Keywords: Ergotherapie